Generating evidence to inform policy and practice: the example of the second generation "atypical" antipsychotics. - Geddes, J (2003)
The introduction of the second generation "atypical" antipsychotics has been heralded as a major advance in the treatment of schizophrenia and other psychotic disorders. Systematic reviews have revealed only modest advantages over conventional antipsychotics and uncertainty about long-term efficacy and safety, yet the second generation antipsychotic drugs have been widely accepted into clinical practice. Although the existing evidence of the benefits and harms of atypical antipsychotics can facilitate decision making about individual patients, the randomized evidence remains inadequate to make valid and fully evidence-based policy statements such as clinical practice guidelines that are designed to apply to groups of patients. Further large randomized trials are needed, but these require patients and clinicians to be in equipoise, or substantially uncertain, about alternative therapies. Premature clinical practice guidelines or expert opinion can lead to changes in clinical practice that make it difficult or impossible to conduct the required trials and are therefore a disservice to patients.